Whistleblowing as a security issue in Hungarian organizations from 2023 - Ilona, Mizser Csilla (2024)
This study aims to provide an overview of the result of the legislative intention, which also set a mandatory deadline for the application of large companies employing more than 250 people, since they must apply Act XXV of 2023 starting from July 24, 2023, on complaints, public interest reports, and the rules on whistleblowing. The purpose of this article is to point out, based on the review of international scientific literature and secondary research, that whistleblowing and reporting are especially supporting tools for organizations, workplaces, employees, and employers. The aim is to emphasize the advantages of organizational security. Presentation of the law created with regard to Hungary's international legal and European Union legal obligations undertaken in connection with actions against corruption. An exhaustive review of the literature on whistleblowing research papers has been conducted. A second study was conducted on regulatory documents, commentaries, and studies. The added value of the paper reflects the relevant legislation and scientific findings in one paper. This paper addresses leaders, employers, employees, university lecturers, and researchers.